Inside or Outside: Origin of Lithium Dendrite Formation of All Solid‐State Electrolytes. Issue 40 (3rd September 2019) - Mo, Fangjie; Ruan, Jiafeng; Sun, Shuxian; Lian, Zixuan; Yang, Sangpu; Yue, Xinyang; Song, Yun; Zhou, Yong‐Ning; Fang, Fang; Sun, Guangai; Peng, Shuming; Sun, Dalin
Abstract: All‐solid‐state lithium metal batteries (ASSLMBs) stand out for the next generation of energy storage system. However, the further realization is severely hampered by the lithium dendrite formation in solid state electrolytes (SSEs), by mechanisms that remain controversial. Herein, with the aid of experimental and theoretical approaches, the origin of dendrite formation in representative LiBH4 SSE, which is thermodynamically stable with the Li metal, suppressing the side reaction between Li and SSE is elucidated. It is demonstrated that upon diffusion, Li + encounters an electron, and is subsequently reduced to Li 0 within the grain boundary/pore of SSE, eventually leading to short circuit. Thus, introducing LiF with the ability of interstitial filling and low electronic conductivity into SSE is the effective countermeasure, and as expected, with the addition of LiF, the critical current density (CCD) increases by 235% compared to the value of pure LiBH4 . The TiS2 |LiBH4 –LiF|Li ASSLMBs manifest a reversible capacity of 137 mAh g −1 at 0.4 C upon 60 cycles. These findings not only unravel critical issues in Li dendrite formation in SSE, but also propose the countermeasure. Abstract : The origin of lithium dendrite formation of all solid‐state electrolytes is revealed using a representative solid‐state electrolyte, LiBH4, which is thermodynamically stable to lithium. It is found that lithium dendrites form inside LiBH4 due to the high electronic conductivity of electrolyte. Decreasing the electronic conductivity of LiBH4 can efficiently improve its dendrite suppression capability.